Biomimetic Synthesis of Ear‐of‐wheat‐shaped Manganese Oxide Nanoparticles on Carbon Nanotubes for High‐capacity Lithium Storage. Issue 3 (7th September 2020) - Sun, Xiaofei; Li, Meijuan; Ndahimana, Anastase; Ding, Peng; Xu, Youlong; Hu, Qiongdan; Chen, Kai; Feng, Tianyu
Abstract : Manganese oxide (Mn3 O4 ) is of great potential for lithium storage based on conversion reactions, but its application in rechargeable lithium batteries is severely hindered by the low electric conductivity and large volume variation during lithiation/delithiation. Herein, a biomimetic ear‐of‐wheat‐like nanocomposite of ultrafine Mn3 O4 nanoparticles (MONPs) and multi‐walled carbon nanotubes (MWCNTs) is prepared using a facile solvothermal method. The tightly packed MONP "cereal‐grains" are directly grown and uniformly interspersed on the outer surface of skeleton MWCNT "central stems." The ultrafine MONPs are favorable to lithium incorporation/extraction while the interconnected MWCNT skeletons provide a highly conducting network for electron transportation. Consequently, a high reversible capacity of 810 mA h g −1 is obtained at the current density of 40 mA g −1 . After 50 cycles at 160 mA g −1, the nanocomposite still delivers a capacity up to 796 mA h g −1, which is higher than twice of that of pure Mn3 O4 nanopowders. The unique nanostructure and the facile biomimetic method can be widely extended to design and explore various high‐performance energy materials for lithium/sodium ion batteries and fuel cells. Abstract : Biomimetic ear‐of‐wheat‐shaped nanocomposite of ultrafine Mn3 O4 nanoparticles (MONPs) with multi‐walled carbon nanotubes (MWCNTs) is prepared by a facile one‐pot solvothermal method. Due to the unique bionic nanostructure, the MWCNTs/MONPs nanocomposite exhibits superior lithium storage performance with high reversible capacities at high charge/discharge rates and good cycling stability at different current densities.